Efek kesehatan dampak suhu ekstrem panas di tempat kerja: Heat stroke - Maharani, Aulia Ikka; Raihanah, Yasmin Jamil; Mubien, Muhammad Fatha (Public Health Risk Assesment Journal, 2024)
This study focuses on the impact of climate change and increasing global temperatures on workers' health, particularly the risk of heat stroke. Climate change has triggered extreme weather and temperature increases, significantly affecting workers in outdoor sectors such as agriculture, industry, fisheries, forestry, and construction. heat stroke is a serious medical condition that occurs when a person's body temperature rises significantly, often as a result of working in high-temperature conditions. This study aims to understand the issues, causes, risk factors, pathophysiology, and prevention methods of heat stroke in the workplace. The results of this research are expected to serve as a reference for companies and workers in dealing with extreme weather and preventing heat stroke.